2018
DOI: 10.1002/cpp.2322
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the dialogue components in Avatar Therapy for schizophrenia patients with refractory auditory hallucinations: A content analysis

Abstract: Auditory verbal hallucinations are hallmark symptoms of schizophrenia and are amongst the most disturbing symptoms of the disorder. Although not entirely understood, the relationship between the voice hearer and their voices has been shown to be an important treatment target. Understanding voice hearers' standpoints through qualitative analysis is central to apprehend a deeper comprehension of their experience and further explore the relevance of interpersonal interventions. Compared with other dialogical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 40 publications
0
23
0
1
Order By: Relevance
“…The therapy may therefore help reduce cognitive avoidance of fear-relevant information (i.e., the voice and its content) and reduce anxiety as a result of exposure 61,62 . A usual therapy experience for patients who engage with the approach generally involves some early anxiety followed by a reported sense of relief, achievement, power, and liberation 56,63,64 . It has been speculated that distressing AVH with negative content may directly impact mood, and low mood may in turn make a patient more vulnerable to further AVH 65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapy may therefore help reduce cognitive avoidance of fear-relevant information (i.e., the voice and its content) and reduce anxiety as a result of exposure 61,62 . A usual therapy experience for patients who engage with the approach generally involves some early anxiety followed by a reported sense of relief, achievement, power, and liberation 56,63,64 . It has been speculated that distressing AVH with negative content may directly impact mood, and low mood may in turn make a patient more vulnerable to further AVH 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Although this study was not conducted with the aim of further understanding the therapeutic elements of the interventions, future research should aim to understand the components of psychotherapies that leads to efficacy over simply conducting efficacy trials. There is indeed emerging work into understanding the therapeutic components that lead to AT's and VRT's large efficacy on AVH and other facets of the illness 63,64 . More research is necessary to establish which components of AT/VRT make it efficacious and to determine which patients may respond better to the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the Avatar Project, virtual reality–assisted therapy for schizophrenia often encourages patients to engage with the voices they hear through the use of an AI avatar. Initial studies found that the therapy could help in developing therapeutic targets [24] and also in particularly difficult cases of schizophrenia [25]. Another study found improvements in auditory visual hallucinations, symptoms of depression, and overall quality of life following therapy sessions for treatment-resistant schizophrenia patients [26].…”
Section: Introductionmentioning
confidence: 99%
“…Higher order themes were in line with key therapeutic processes of the interventions. For CBT, these themes were based on the topics discussed during the intervention (e.g., normalization of voices, coping strategies) and for VRT, the themes were based on prior qualitative analyses (e.g., emotion regulation, self-perceptions) [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, VRT is among a newer wave of dialogical approaches that aim to ameliorate the voice-hearer relationship by encouraging assertive interactions with voices and by negotiating new ways of relating. VRT focusses on repetitive practice in real-time in an emotional-inducing VR environment where patients may dialogue with their distressing voices [ 28 , 29 , 30 , 34 , 35 ]. Although these two therapies overlap in common practice, to our knowledge, no one has integrated both these models to draw on their strengths.…”
Section: Introductionmentioning
confidence: 99%